Synthesis of walnut‐like polyaniline by using polyvinyl alcohol micellar template with excellent film transmission. Issue 29 (17th March 2021) - Wang, Wenjiao; Ma, Yong; Zhuang, Zhao; Zhou, Shujie; Ma, Mingliang; Wu, Qi; Bai, Ruiqin; Li, Tingxi
Abstract: Though there have been many reports on various morphologies of polyaniline (PANI), the research on fabricating new morphologies remains to be explored. In this work, with the help of polyvinyl alcohol (PVA) micelles as templates, walnut‐like PANI having a rough periphery is successfully synthesized at room temperature by a static reaction. In addition, the effects of the amount of PVA, the concentration of HCl solution and the type of surfactant on the morphologies of PANI are studied in detail. Outcomes demonstrate that the fabrication of PANI walnuts is a result of the cooperation effect of the amount of PVA and the concentration of HCl solution. Moreover, PANI walnuts exhibit good thermal stability, which begins to degrade at up to about 300°C. Thin film coated by PANI walnuts possesses excellent transmittance. When PANI sample is prepared in the presence of 0.50 g PVA and 0.010 M HCl solution, the film transmittance can reach a maximum of 74% at 1200 nm. The sample presented herein have potential to be used in optical devices. Abstract : By changing the types of surfactants, PANI can be obtained in walnut, coral, and irregular block shapes. And the size of walnut‐like polyaniline can be controlled by adjusting the amount of PVA added and the concentration of hydrochloric acid.